2016
DOI: 10.1007/s10633-016-9535-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-color pupillometry in enhanced S-cone syndrome caused by NR2E3 mutations

Abstract: Purpose: The purpose of this study was to evaluate pupillary light reflexes (PLRs) mediated by rod, cone, and intrinsically photosensitive retinal ganglion cell pathways as indices of outer- and inner-retinal function in patients who have enhanced S-cone syndrome (ESCS) due to NR2E3 mutations. Methods: Four patients with ESCS (ages 16-23 years) participated in the study. Subjects were tested with long- and short-wavelength single-flash full-field ERG stimuli under light adapted conditions. They were also tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…The previously reported mutations were as follows: c.226C > T, p.(R76W), was seen in patient I; c.119-2A > C was seen as homozygous in patient II and heterozygous in patient III ( Table 1). All three patients showed signs of pigment clumping that extended in a band from the vascular arcades to the mid-periphery with a characteristic corresponding band of a decreased signal in AF extending from the vascular arcades to the mid periphery, which is consistent with the literature regarding patients with recessive NR2E3 mutations [3,8,19,35,[38][39][40][41]. An increased macular AF signal was also noted.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The previously reported mutations were as follows: c.226C > T, p.(R76W), was seen in patient I; c.119-2A > C was seen as homozygous in patient II and heterozygous in patient III ( Table 1). All three patients showed signs of pigment clumping that extended in a band from the vascular arcades to the mid-periphery with a characteristic corresponding band of a decreased signal in AF extending from the vascular arcades to the mid periphery, which is consistent with the literature regarding patients with recessive NR2E3 mutations [3,8,19,35,[38][39][40][41]. An increased macular AF signal was also noted.…”
Section: Discussionsupporting
confidence: 89%
“…CPRD typically shows clinically visible clumped pigmentation in the mid-peripheral fundus in all four quadrants and is associated with minimal evidence of bone spicule pigmentation [16]. More recently, it has been suggested that GFS and clumped pigmentary retinopathy associated with NR2E3 mutations could be considered part of the expanded phenotype of ESCS; both conditions share similar electrophysiological features to ESCS [8,[17][18][19][20]. The NR2E3 gene was identified by Kobayashi and colleagues in 1999 it is located on chromosome 15q23, comprises eight exons, spans approximately 7.7kb of genomic DNA and encodes a 410-amino acid protein ( Figure 1) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the relative transient and sustained pupil response to red and blue lights in healthy control subjects, Lorenz et al, (2012) reported no significant differences in pupil contraction for stimulation of cones. In agreement with this, Collison et al (2016) compared the magnitude of the light-adapted red and blue ERG waves and the per cent change in transient pupil constriction in healthy control subjects, and as in our study, he found that red light produces smaller ERG (a-wave: 46-94, b-wave: 146-261) than blue light (a-wave: 55-92, b-wave: 168-261) and that the per cent change in pupil size (i.e. constriction) for cones was 37-55% for red and 38-55% for blue (i.e.…”
Section: Sirsupporting
confidence: 81%
“…Relatively recent advances in the understanding of the neural mechanisms that mediate the pupil response have greatly renewed interest in pupillometry as a tool for assessing retinal function in patients with acquired91011 and inherited12131415 retinal disease. That is, the afferent limb of the pupillary response to light is now thought to be driven primarily by intrinsically photosensitive retinal ganglion cells (ipRGCs) that contain the photopigment melanopsin1617.…”
mentioning
confidence: 99%